The Role of Inflation, SBI Interest Rates, and The Dollar Exchange Rate In Influencing The Composite Stock Price Index (IHSG) Study In 2020-2023 - Ofika, Tentria Oking; Supheni, Indrian; Rahayu, Dwi Puji (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives : This study aims to analyze the simultaneous and partial influence of macroeconomic indicators—namely inflation, SBI (Bank Indonesia Certificate) interest rates, and the USD/IDR exchange rate—on the Jakarta Composite Index (JCI) during the 2020–2023 period. Method : This quantitative study employs secondary monthly time series data (n = 43) from January 2020 to July 2023. Data were sourced from official databases (BI, BPS, IDX) and analyzed using multiple linear regression. Classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity were performed to validate the model. Research Findings : The results indicate that inflation has a significant positive effect on the JCI, while the SBI interest rate and USD exchange rate have a significant negative effect. Simultaneously, the three variables significantly influence the JCI, explaining 49.7% of its variation. Theoretical Contribution / Originality : The study contributes to signaling theory by confirming that macroeconomic indicators serve as important signals to investors in stock market decision-making. It also enriches empirical literature with mixed findings on inflation’s role in equity markets. Practitioner / Policy Implications : Findings suggest that policymakers and investors should closely monitor inflation trends and interest rate movements to anticipate capital market dynamics. BI rate policy shifts and exchange rate volatility directly impact investment behavior in Indonesia. Research limitations : The study is limited by the use of monthly secondary data and a short observation period during extraordinary events (COVID-19, geopolitical tensions), which may influence generalizability.